Targeted depletion of RibF, a putative bifunctional FAD synthetase/ flavokinase in Mycobacterium smegmatis using CRISPR interference - Raphela, Mabule Lucas (Department of Clinical Laboratory Sciences, 2021)
Tuberculosis (TB) is the leading killer globally owing to an infectious disease. There is consequently an urgent need to develop novel TB drugs and shorter regimens to treat the causative agent, Mycobacterium tuberculosis, an imperative which demands the identification of new drug targets in essential mycobacterial pathways. To that end, the work presented in this dissertation aimed to functionally characterize ribF, an essential gene in the mycobacterial riboflavin (RF; vitamin B2) biosynthetic pathway. Given the role of RF as a core component of the essential flavin cofactors, flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD), it was hypothesized that silencing ribF would disrupt the biosynthesis of all flavoproteins, crippling numerous (essential) processes within the organism. Moreover, based on previous observations in Bacillus subtilis, it was predicted that the mycobacterial ribF homolog might play a role in regulating the rib operon (comprising a cluster of RF pathway genes) – either directly by binding to the FMN riboswitch, or indirectly through the production of FMN from RF, in turn enabling riboswitch-mediated repression of downstream genes. CRISPR interference (CRISPRi) technology was used to generate an anhydrotetracycline (ATc)-inducible ribF hypomorph of M. smegmatis, a widely exploited mycobacterial model. Consistent with other organisms, ribF was shown to be essential for in vitro growth of M. smegmatis: CRISPRi-mediated depletion of ribF was bacteriostatic, resulting in a 10-fold growth inhibition in liquid media and corresponding to no reduction (0 log-fold change) in colony forming units (CFU). Moreover, targeted metabolomic analyses revealed that ribF depletion was associated with accumulation of 6,7-Dimethylribityllumazine (DMRL), suggesting that the disruption of RibF function blocked conversion of RF to the essential cofactors, FMN and FAD, in turn inhibiting cell growth. Notably, the lethality of ribF depletion could not be complemented chemically by exogenous supplementation of growth media with RF, FMN or FAD. Downregulation of ribF also caused enhanced susceptibility to the known cell wall-targeting agent, vancomycin, but not to the putative RibF domain inhibitor, thonzonium bromide, suggesting an alternative mechanism of action or impaired bacillary permeation. In summary, these data support the inferred essentiality of ribF in mycobacteria, in turn supporting future work which aims to target this enzyme for new TB drug discovery.